Cervantes’ justice: judges and trials in Don Quixote de la Mancha - Jocelyn-Holt, Emilia (2021)
This article is a first approach to the study of Miguel de Cervantes’ notion of justice in his novel Don Quixote de la Mancha. To this end, it reflects on the application of justice, particularly concerning three judges who appear in one way or another: Don Quixote, Sancho Panza, and Cervantes himself. In the character of Don Quixote, we see a model of justice already surpassed, while in Sancho Panza we are presented with a model of the judge, which sadly is nothing more than a great mockery. Finally, Cervantes is analyzed as a judge to ask whether the author condemns or absolves justice as an ideal.